Synthesis and Biological Activity of 3-Chloro-1-(4-perimidine methylcarbonylamino)-4-phenyl-azetidin-2-one - Dinesh R. Panchasara; Subhash Pande (E-Journal of Chemistry)
Perimidine-1-acetic acid hydrazide (1) undergoes facile condensation with aromatic aldehydes to afford the corresponding azomethine (i.e. Schiff base) derivatives (2a-h) in good yield. Cyclocondensation of compounds (2a-h) with chloro acetyl chloride affords 3-chloro-1-(4-perimidine methylcarbonylamino)-4-phenyl-azetidin-2-ones (3a-h). The structures of these compounds were established on the basis of analytical and spectral data. The newly synthesized compounds were evaluated for their antibacterial and antifungal activities.